Sludge-based catalytic material as well as preparation method and application thereof

Through modification treatment and pyrolysis treatment of sludge, sludge-based catalytic materials with high specific surface area and rich oxygen-containing functional groups were prepared, which solved the problem of insufficient performance of existing sludge-based biochar, and achieved efficient treatment of printing and dyeing wastewater and efficient utilization of sludge.

CN119524924APending Publication Date: 2025-02-28江苏环保产业技术研究院股份公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411578575.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The specific surface area and pore structure of existing sludge-based biochar are poor, resulting in low potential as a pollutant adsorbent and catalyst carrier. At the same time, it cannot effectively control the distribution of metal elements in the sludge and cannot achieve efficient utilization of sludge.

Method used

Sludge particles are obtained by drying the sludge treatment, and then mixed with EDTA, citric acid and water for reaction, modifying the sludge particles, and then mixing with phosphomolybdic acid solution for pyrolysis to produce sludge-based catalytic material with a high specific surface area and rich oxygen-containing functional groups.

Benefits of technology

The adsorption capacity and catalytic degradation capacity of sludge-based catalytic materials are improved, so that they can effectively treat printing and dyeing wastewater, reduce environmental pollution, and achieve efficient utilization of sludge.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental functional materials, and discloses a sludge-based catalytic material as well as a preparation method and application thereof. The preparation method of the sludge-based catalytic material comprises the following steps: drying sludge to obtain sludge particles; mixing the sludge particles, EDTA (Ethylene Diamine Tetraacetic Acid), citric acid and water, and reacting to obtain modified sludge particles; mixing the modified sludge with a phosphomolybdic acid solution, and performing pyrolysis to obtain the sludge-based catalytic material. According to the invention, the EDTA and the citric acid are adopted to modify the sludge, metals in the sludge are distributed on the surface of the material in the subsequent pyrolysis process, and the citric acid also has a pore-forming effect to increase the specific surface area of the material and improve the adsorption capacity to pollutants; the sludge is modified by adopting phosphomolybdic acid, and abundant oxygen-containing functional groups are introduced to the surface of sludge carbon, so that the adsorption capacity and the catalytic degradation capacity of the sludge-based catalytic material are improved, and the sludge-based catalytic material has good catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental functional materials, and in particular to a sludge-based catalytic material and a preparation method and application thereof. Background Art

[0002] Printing and dyeing wastewater is difficult to treat due to its high chroma, complex composition and high COD content. Methylene blue is a representative of azo dyes. It has an aromatic structure that is difficult to destroy and is difficult to degrade by traditional methods. The main treatment methods currently include physical, chemical and biological methods. The use of adsorption methods to remove dyes from printing and dyeing wastewater has been widely used. In addition, advanced oxidation technology has also received widespread attention in the removal of printing and dyeing wastewater due to its advantages of being able to directly mineralize organic matter or improve its biodegradability.

[0003] Faced with the rapid development of industry and the acceleration of urbanization, the amount of toxic and hazardous solid waste generated has increased rapidly. The safe disposal of "bulk solid waste" in the field of industrial production is very severe. In addition to harmful heavy metal tailings, coal gangue, smelting slag, phosphogypsum, red mud and calcium carbide slag in traditional industries, it also includes heavy metal sludge from industrial sources. There are many methods for treating heavy metal sludge, such as resource utilization, solidification landfill, incineration disposal and cement kiln co-disposal. Among them, resource utilization includes two categories: pyrolysis and hydrolysis: the pyrolysis process consumes a lot of energy, causes serious pollution, and has a low resource utilization rate. At present, research has found that sludge-based biochar can be used to treat printing and dyeing wastewater. However, the specific surface area and pore structure of sludge-based biochar are poor, and its potential as a pollutant adsorbent and catalyst carrier is low. At the same time, the distribution of metal elements in sludge cannot be controlled, and the efficient utilization of sludge cannot be achieved.

[0004] At present, how to improve the adsorption and catalytic degradation capacity of sludge carbon for printing and dyeing wastewater is of great significance for reducing environmental pollution and achieving the goal of treating waste with waste. Summary of the invention

[0005] The object of the present invention is to provide a sludge-based catalytic material and a preparation method and application thereof, so as to solve the problems existing in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a sludge-based catalytic material, comprising the following steps:

[0008] (1) Drying the sludge to obtain sludge particles;

[0009] (2) mixing the sludge particles, EDTA, citric acid and water to react and obtain modified sludge particles;

[0010] (3) The modified sludge particles are mixed with a phosphomolybdic acid solution and pyrolyzed to obtain a sludge-based catalytic material.

[0011] Preferably, in the above-mentioned method for preparing a sludge-based catalytic material, the temperature of the drying treatment in step (1) is 80 to 110° C., and the time of the drying treatment in step (1) is 12 to 24 hours.

[0012] Preferably, in the above-mentioned method for preparing a sludge-based catalytic material, the usage ratio of the sludge particles, EDTA, citric acid and water in step (2) is 1-10 g: 10-50 g: 10-50 g: 100-200 mL.

[0013] Preferably, in the above-mentioned method for preparing a sludge-based catalytic material, the reaction temperature in step (2) is 30 to 40° C., and the reaction time in step (2) is 10 to 24 hours.

[0014] Preferably, in the above-mentioned method for preparing a sludge-based catalytic material, the ratio of the modified sludge particles to the phosphomolybdic acid solution in step (3) is 3-8 g: 100-150 mL;

[0015] The concentration of the phosphomolybdic acid solution in step (3) is 3-5 mg / mL.

[0016] Preferably, in the above-mentioned method for preparing a sludge-based catalytic material, the pyrolysis conditions in step (3) are: a heating rate of 4 to 9°C / min, a temperature of 200 to 300°C, and a time of 3 to 4h.

[0017] The invention also provides a sludge-based catalytic material prepared by the method for preparing the sludge-based catalytic material.

[0018] The invention also provides an application of a sludge-based catalytic material in treating printing and dyeing wastewater.

[0019] Preferably, in the above application, the application method comprises the following steps:

[0020] The printing and dyeing wastewater is mixed with the sludge-based catalytic material to obtain a mixed solution; a hydrochloric acid solution is added to the mixed solution to adjust the pH of the mixed solution to be acidic, and then an H2O2 solution is added to react.

[0021] Preferably, in the above application, the usage ratio of the printing and dyeing wastewater to the sludge-based catalytic material is 100-150 mL: 10-50 mg;

[0022] The volume ratio of the printing and dyeing wastewater to the H2O2 solution is 20-30:1-2;

[0023] The concentration of the H2O2 solution is 25-35 wt%.

[0024] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) In the present invention, EDTA and citric acid are used to modify the sludge. EDTA and citric acid have good complexing ability for metals in the sludge. In the subsequent pyrolysis process, the metals in the sludge are distributed on the surface of the sludge carbon. Citric acid also has a pore-forming effect to increase the specific surface area of ​​the sludge carbon and improve the adsorption capacity for pollutants. At the same time, phosphomolybdic acid is used to modify the sludge under low-temperature (200-300°C) pyrolysis conditions. Phosphomolybdic acid has high oxidation activity and acidity, and rich oxygen-containing functional groups are introduced on the surface of the sludge carbon. The introduction of oxygen-containing functional groups provides sufficient chemical adsorption sites for the sludge-based catalytic material. At the same time, the oxygen-containing functional groups serve as active sites to enable the sludge-based catalytic material to have certain catalytic performance, thereby improving the adsorption capacity and catalytic degradation capacity of the sludge-based catalytic material, and making the sludge-based catalytic material have good catalytic performance.

[0026] (2) In the present invention, the surface functional groups of the sludge-based catalytic material enrich methylene blue on the surface of the sludge-based catalytic material through conjugation and hydrogen bonding, and then the oxygen-containing functional groups on the surface of the sludge-based catalytic material synergistically act with metal ions to activate H2O2 to generate hydroxyl radicals, thereby achieving the treatment of printing and dyeing wastewater. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a sludge-based catalytic material, comprising the following steps:

[0028] (1) Drying the sludge to obtain sludge particles;

[0029] (2) mixing the sludge particles, EDTA, citric acid and water to react and obtain modified sludge particles;

[0030] (3) The modified sludge particles are mixed with a phosphomolybdic acid solution and pyrolyzed to obtain a sludge-based catalytic material.

[0031] In the present invention, the temperature of the drying treatment in step (1) is preferably 80-110°C, more preferably 85-105°C, and more preferably 90-100°C; the time of the drying treatment in step (1) is preferably 12-24h, more preferably 15-20h, and more preferably 16-18h.

[0032] In the present invention, the dosage ratio of the sludge particles, EDTA, citric acid and water in step (2) is preferably 1-10 g: 10-50 g: 10-50 g: 100-200 mL, more preferably 3-8 g: 15-40 g: 15-45 g: 120-180 mL, and more preferably 4-6 g: 20-30 g: 20-30 g: 150-170 mL.

[0033] In the present invention, the reaction temperature in step (2) is preferably 30-40°C, more preferably 32-38°C, and more preferably 35-36°C; the reaction time in step (2) is preferably 10-24h, more preferably 12-20h, and more preferably 15-18h.

[0034] In the present invention, after the reaction in step (2) is completed, the process further comprises:

[0035] The obtained product is washed with water, and then dried after washing;

[0036] The drying temperature is preferably 80 to 120° C., more preferably 85 to 110° C., and more preferably 90 to 100° C.; the drying time is preferably 12 to 24 hours, more preferably 15 to 20 hours, and more preferably 16 to 18 hours.

[0037] In the present invention, the dosage ratio of the modified sludge particles to the phosphomolybdic acid solution in step (3) is preferably 3-8 g: 100-150 mL, more preferably 4-7 g: 110-140 mL, and more preferably 5-6 g: 120-130 mL;

[0038] The concentration of the phosphomolybdic acid solution in step (3) is preferably 3 to 5 mg / mL, more preferably 3.5 to 4.5 mg / mL, and more preferably 3.8 to 4.2 mg / mL.

[0039] In the present invention, the conditions for pyrolysis in step (3) are: the heating rate is preferably 4-9°C / min, more preferably 5-8°C / min, more preferably 6-7°C / min; the temperature is preferably 200-300°C, more preferably 220-280°C, more preferably 250-260°C; the time is preferably 3-4h, more preferably 3.25-3.75h, more preferably 3.5h.

[0040] In the present invention, after the pyrolysis in step (3) is completed, the process further comprises:

[0041] The obtained product is cooled to room temperature and then washed with water, and then dried and sieved after washing;

[0042] The drying temperature is preferably 80 to 120° C., more preferably 85 to 110° C., and more preferably 90 to 100° C.; the drying time is preferably 12 to 24 hours, more preferably 15 to 20 hours, and more preferably 16 to 18 hours.

[0043] The invention also provides a sludge-based catalytic material prepared by the method for preparing the sludge-based catalytic material.

[0044] The invention also provides an application of a sludge-based catalytic material in treating printing and dyeing wastewater.

[0045] In the present invention, the application method comprises the following steps:

[0046] The printing and dyeing wastewater is mixed with the sludge-based catalytic material to obtain a mixed solution; a hydrochloric acid solution is added to the mixed solution to adjust the pH of the mixed solution to be acidic, and then an H2O2 solution is added to react.

[0047] In the present invention, the usage ratio of the printing and dyeing wastewater to the sludge-based catalytic material is preferably 100-150 mL: 10-50 mg, more preferably 110-140 mL: 15-45 mg, and more preferably 120-130 mL: 20-30 mg.

[0048] In the present invention, the volume ratio of the printing and dyeing wastewater to the H2O2 solution is preferably 20-30:1-2, more preferably 22-28:1.2-1.7, and more preferably 25-26:1.4-1.5;

[0049] The concentration of the H2O2 solution is preferably 25-35 wt%, more preferably 28-32 wt%, and more preferably 30 wt%.

[0050] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] The sludge described in the following embodiments comes from a wastewater treatment plant in a surface treatment park, with a moisture content of about 65%. The dry sludge contains 5.74% chromium, 7.7% iron, 0.54% copper, 0.54% nickel, 3.87% zinc, and heavy metals in the form of sulfides account for 0.8% of the total amount of corresponding heavy metals.

[0052] Example 1

[0053] (1) Drying 20 g of sludge at 100°C for 15 h to obtain sludge particles;

[0054] (2) 20 g EDTA, 40 g citric acid and 150 mL water were mixed, 10 g sludge particles were added, and the mixture was reacted at 40 °C for 12 h. After the reaction, the obtained product was washed with clean water and dried at 80 °C for 12 h to obtain modified sludge particles.

[0055] (3) 5 g of modified sludge particles were mixed with 100 mL of 3 mg / mL phosphomolybdic acid solution, and the temperature was raised to 240 °C at a heating rate of 5 °C / min for pyrolysis for 3.5 h. After the pyrolysis, the mixture was cooled to room temperature and the obtained product was washed with clean water. After washing, the mixture was dried at 100 °C for 14 h and then sieved through a 200-mesh sieve to obtain a sludge-based catalytic material.

[0056] Example 2

[0057] (1) Drying 20 g of sludge at 80°C for 24 h to obtain sludge particles;

[0058] (2) 10 g EDTA, 30 g citric acid and 150 mL water were mixed, 10 g sludge particles were added, and the mixture was reacted at 30 ° C for 20 h. After the reaction, the obtained product was washed with clean water and dried at 120 ° C for 12 h to obtain modified sludge particles;

[0059] (3) 5 g of modified sludge particles were mixed with 100 mL of 5 mg / mL phosphomolybdic acid solution, and the temperature was raised to 300 °C at a heating rate of 9 °C / min for pyrolysis for 4 h. After the pyrolysis, the mixture was cooled to room temperature and washed with clean water. After washing, the mixture was dried at 120 °C for 12 h and then sieved through a 200-mesh sieve to obtain a sludge-based catalytic material.

[0060] Example 3

[0061] (1) Drying 20 g of sludge at 90°C for 18 h to obtain sludge particles;

[0062] (2) 30 g EDTA, 20 g citric acid and 150 mL water were mixed, 10 g sludge particles were added, and the mixture was reacted at 38 °C for 20 h. After the reaction, the obtained product was washed with clean water and dried at 100 °C for 15 h to obtain modified sludge particles;

[0063] (3) 5 g of modified sludge particles were mixed with 100 mL of 4.5 mg / mL phosphomolybdic acid solution, and the temperature was raised to 240 °C at a heating rate of 6 °C / min for pyrolysis for 3 h. After the pyrolysis, the mixture was cooled to room temperature and the obtained product was washed with clean water. After washing, the mixture was dried at 110 °C for 15 h and then passed through a 200-mesh sieve to obtain a sludge-based catalytic material.

[0064] Example 4

[0065] (1) Drying 20 g of sludge at 100°C for 20 h to obtain sludge particles;

[0066] (2) 10 g EDTA, 40 g citric acid and 150 mL water were mixed, 10 g sludge particles were added, and the mixture was reacted at 32 °C for 24 h. After the reaction, the obtained product was washed with clean water and dried at 100 °C for 20 h to obtain modified sludge particles.

[0067] (3) 5 g of modified sludge particles were mixed with 100 mL of 5 mg / mL phosphomolybdic acid solution, and the temperature was raised to 280 °C at a heating rate of 6 °C / min for pyrolysis for 3.5 h. After the pyrolysis, the mixture was cooled to room temperature and the product was washed with clean water. After washing, the product was dried at 120 °C for 12 h and then sieved through a 200-mesh sieve to obtain a sludge-based catalytic material.

[0068] Comparative Example 1

[0069] (1) Drying 20 g of sludge at 100°C for 15 h to obtain sludge particles;

[0070] (3) 5 g of sludge particles were mixed with 100 mL of 3 mg / mL phosphomolybdic acid solution, and the temperature was raised to 240 °C at a heating rate of 5 °C / min for pyrolysis for 3.5 h. After the pyrolysis, the mixture was cooled to room temperature, and the obtained product was washed with clean water. After washing, it was dried at 100 °C for 14 h, and then passed through a 200-mesh sieve to obtain a sludge-based catalytic material.

[0071] Comparative Example 2

[0072] (1) Drying 20 g of sludge at 100°C for 15 h to obtain sludge particles;

[0073] (2) 20 g of EDTA, 40 g of citric acid and 150 mL of water were mixed, 10 g of sludge particles were added, and the mixture was reacted at 40 °C for 12 h. After the reaction, the obtained product was washed with clean water and dried at 80 °C for 12 h to obtain a sludge-based catalytic material.

[0074] The effluent from the printing and dyeing wastewater treated in the following application example has the following indicators: COD is 300 mg / L, chromaticity is 280 times, and aniline concentration is 2.74 mg / L.

[0075] Application Example 1

[0076] At 25°C, 50 mg of the sludge-based catalytic material prepared in Example 1 was added to 100 mL of printing and dyeing wastewater to obtain a mixed solution, and the pH of the mixed solution was adjusted to 4 with a 0.1 mol / L hydrochloric acid solution, and then 2 mL of a 30 wt% H2O2 solution was added, and the mixture was stirred at a speed of 200 r / min for 25 h. After the reaction was completed, the filtrate was filtered to obtain a filtrate, and its absorbance was tested at a wavelength of 664 nm;

[0077] After testing, the COD of the treated printing and dyeing wastewater was 100 mg / L, the chromaticity was 32 times, and the aniline concentration was 0 mg / L.

[0078] Application Example 2

[0079] At 25°C, 50 mg of the sludge-based catalytic material prepared in Example 2 was added to 100 mL of printing and dyeing wastewater to obtain a mixed solution, and the pH of the mixed solution was adjusted to 4 with a 0.1 mol / L hydrochloric acid solution, and then 2 mL of a 30 wt% H2O2 solution was added, and the mixture was stirred at a speed of 200 r / min for 25 h. After the reaction was completed, the filtrate was filtered to obtain a filtrate, and its absorbance was tested at a wavelength of 664 nm;

[0080] After testing, the COD of the treated printing and dyeing wastewater was 110 mg / L, the chromaticity was 35 times, and the aniline concentration was 0 mg / L.

[0081] Application Example 3

[0082] At 25°C, 50 mg of the sludge-based catalytic material prepared in Example 3 was added to 100 mL of printing and dyeing wastewater to obtain a mixed solution, and the pH of the mixed solution was adjusted to 4 with a 0.1 mol / L hydrochloric acid solution, and then 2 mL of a 30 wt% H2O2 solution was added, and the mixture was stirred at a speed of 200 r / min for 25 h. After the reaction was completed, the filtrate was filtered to obtain a filtrate, and its absorbance was tested at a wavelength of 664 nm;

[0083] After testing, the COD of the treated printing and dyeing wastewater was 90 mg / L, the chromaticity was 30 times, and the aniline concentration was 0 mg / L.

[0084] Application Example 4

[0085] At 25°C, 50 mg of the sludge-based catalytic material prepared in Example 4 was added to 100 mL of printing and dyeing wastewater to obtain a mixed solution, and the pH of the mixed solution was adjusted to 4 with a 0.1 mol / L hydrochloric acid solution, and then 2 mL of a 30 wt% H2O2 solution was added, and the mixture was stirred at a speed of 200 r / min for 25 h. After the reaction was completed, the filtrate was filtered to obtain a filtrate, and its absorbance was tested at a wavelength of 664 nm;

[0086] After testing, the COD of the treated printing and dyeing wastewater was 100 mg / L, the chromaticity was 31 times, and the aniline concentration was 0 mg / L.

[0087] Application Example 5

[0088] At 25°C, 50 mg of the sludge-based catalytic material prepared in Comparative Example 1 was added to 100 mL of printing and dyeing wastewater to obtain a mixed solution, and the pH of the mixed solution was adjusted to 4 with a 0.1 mol / L hydrochloric acid solution, and then 2 mL of a 30 wt% H2O2 solution was added, and the mixture was stirred at a speed of 200 r / min for 25 hours. After the reaction was completed, the filtrate was filtered to obtain a filtrate, and its absorbance was tested at a wavelength of 664 nm;

[0089] After testing, the COD of the treated printing and dyeing wastewater was 200 mg / L, the chromaticity was 100 times, and the aniline concentration was 0.5 mg / L.

[0090] Application Example 6

[0091] At 25°C, 50 mg of the sludge-based catalytic material prepared in Comparative Example 2 was added to 100 mL of printing and dyeing wastewater to obtain a mixed solution, and the pH of the mixed solution was adjusted to 4 with a 0.1 mol / L hydrochloric acid solution, and then 2 mL of a 30 wt% H2O2 solution was added, and the mixture was stirred at a speed of 200 r / min for 25 h. After the reaction was completed, the filtrate was filtered to obtain a filtrate, and its absorbance was tested at a wavelength of 664 nm;

[0092] After testing, the COD of the treated printing and dyeing wastewater was 220 mg / L, the chromaticity was 130 times, and the aniline concentration was 0.9 mg / L.

[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a sludge-based catalytic material, characterized in that: The following steps are involved: (1) Drying the sludge to obtain sludge particles; (2) mixing the sludge particles, EDTA, citric acid and water to react and obtain modified sludge particles; (3) The modified sludge particles are mixed with a phosphomolybdic acid solution and pyrolyzed to obtain a sludge-based catalytic material.

2. The method for preparing the sludge-based catalytic material according to claim 1, characterized in that: The temperature of the drying treatment in step (1) is 80 to 110° C., and the time of the drying treatment in step (1) is 12 to 24 hours.

3. The method for preparing the sludge-based catalytic material according to claim 2, characterized in that: The dosage ratio of the sludge particles, EDTA, citric acid and water in step (2) is 1-10 g: 10-50 g: 10-50 g: 100-200 mL.

4. The method for preparing the sludge-based catalytic material according to claim 3, characterized in that: The reaction temperature in step (2) is 30-40° C., and the reaction time in step (2) is 10-24 h.

5. The method for preparing the sludge-based catalytic material according to claim 3 or 4, characterized in that: The ratio of the modified sludge particles to the phosphomolybdic acid solution in step (3) is 3-8 g: 100-150 mL; The concentration of the phosphomolybdic acid solution in step (3) is 3-5 mg / mL.

6. The method for preparing the sludge-based catalytic material according to claim 5, characterized in that: The pyrolysis conditions in step (3) are as follows: a heating rate of 4 to 9°C / min, a temperature of 200 to 300°C, and a time of 3 to 4h.

7. The sludge-based catalytic material obtained by the method for preparing the sludge-based catalytic material according to any one of claims 1 to 6.

8. Use of the sludge-based catalytic material according to claim 7 in treating printing and dyeing wastewater.

9. The use according to claim 8, characterized in that: The application method comprises the following steps: The printing and dyeing wastewater is mixed with the sludge-based catalytic material to obtain a mixed solution; a hydrochloric acid solution is added to the mixed solution to adjust the pH of the mixed solution to be acidic, and then an H2O2 solution is added to react.

10. The use according to claim 9, characterized in that: The dosage ratio of the printing and dyeing wastewater to the sludge-based catalytic material is 100-150 mL: 10-50 mg; The volume ratio of the printing and dyeing wastewater to the H2O2 solution is 20-30:1-2; The concentration of the H2O2 solution is 25-35 wt%.

Citation Information

Cited By

  • Biochar-loaded molybdenite adsorbent as well as preparation method and application thereof

    CN120790105A